Anodized TiO2 nanotubes coated with Pt nanoparticles for enhanced photoelectrocatalytic activity. Issue 4 (5th January 2017) - Liu, Yan; Su, Dong; Zhang, Yanzong; Wang, Lilin; Yang, Gang; Shen, Fei; Deng, Shihuai; Zhang, Xiaohong; Zhang, Shirong
Abstract: Abstract : TiO2 nanotubes have been demonstrated with promising future in photoelectrocatalytic (PEC)_ applications and deposition of Pt nanoparticles on TiO2 has been widely used to enhance their PEC activities. However, those Pt nanoparticles are normally randomly deposited on the surface of TiO2 nanotubes. Selective deposition of Pt nanoparticles is important to achieve better charge separation. In this study, we reported an electrochemical activation step to prepare TiO2 nanotubes deposited with Pt nanoparticles on their open ends. The "activation step" played a key role in achieving a clean surface of the TiO2 nanotubes, thus ensuring the uniform growth of Pt nanoparticles and efficient photogenerated electrons transportation. The Pt-A-TiO2 films have photocatalytic activities in hydrogen generation and methyl orange degradation with a high hydrogen generation rate of 0.74 mL/h/cm 2, three times that of the pure TiO2 nanotubes (0.24 mL/h/cm 2 ). Thus, this study demonstrated an effective method for improving the performance of Pt/TiO2 photocatalyst.